The Borda and Condorcet winners coincide for lexicographic preferences. - Salmaso, Pietro; Moreno-Jiménez, Bernardo (Elsevier, 2024)
We show that, for any lexicographic preference profile, the sets of Borda and Condorcet winners coincide. Moreover, the sets of Borda and Condorcet losers also coincide. However the binary relations induced by the Borda Count and the majority pairwise comparisons are not the same.
https://openpolicyfinder.jisc.ac.uk/id/publication/15557
Keywords: Elecciones - Modelos matemáticos; Lexicographical preferences; Condorcet winner; Borda winner